The concerns of mechanical upper urinary tract obstruction in neurogenic lower urinary tract dysfunction: Beyond augmentation cystoplasty - Zhou, Zhonghan; Wang, Xuesheng; Liao, Limin (Frontiers in Surgery, 2023)
Purpose: To evaluate the efficacy of augmentation uretero-enterocystoplasty (AUEC), a modified surgical procedure that highlights the mobilization of the ureter and the necessity of ureteroplasty in a series of neurogenic lower urinary tract dysfunction (NLUTD) patients with mechanical upper urinary tract obstruction (mUUTO). Methods: We retrospectively reviewed the medical records of NLUTD patients who underwent an AUEC from 2005 to 2022. mUUTO was diagnosed by preoperative bladder drainage, magnetic resonance urography (MRU), and isotope renography. Upper urinary tract dilatation (UUTD) was evaluated using MRU with the Liao MRU-UUTD system. Results: A total of 58 patients and 103 ureters with the presence of mUUTO were analyzed. Improvement in maximum bladder capacity, maximum detrusor pressure and bladder compliance, and stabilization of serum creatine were observed. The proportion of high-grade UUTD was significantly reduced after the surgery, and the typical preoperative obstruction imaging disappeared. Conclusion: Beyond traditional augmentation cystoplasty, more attention should be paid to the release of mUUTO and mobilization of the ureter in NLUTD patients.